Kumar and Clark's Clinical Medicine - Kumar, P. Parveen; Clark, M. Michael (International edition, 2017)
The ninth edition of this best-selling textbook of clinical medicine builds even further on its formidable, prize-winning formula of excellence, comprehensiveness and accessibility. 'This book is stunning in its breadth and ease-of-use. It still remains the "gold standard", thorough guide to clinical medicine its forefathers were.' BMA Medical Book Awards judges. New to this edition: *2 new chapters: Global Health and Women's Health. *25 new authors. * New online editor, Adam Feather, with a team of young doctors to augment the e-book which accompanies the print book with clinical tips, key learning points, drug tips, learning challenges, case studies and MCQs. * Full text redesign to incorporate: New system overview diagrams for clinical chapters. New coloured headings to help identify content relating to disease, management, investigations etc. New icons to aid text navigation. 11 new members and a new co-editor, Senaka Rajapakse, of the International Advisory Board.